Longitudinal relations between children's cognitive and affective theory of mind with reactive and proactive aggression. Issue 5 (20th February 2017) - Austin, Gina; Bondü, Rebecca; Elsner, Birgit
Abstract : Aggression may be performed for different reasons, such as defending oneself (reactive aggression) or to reach egoistic aims (proactive aggression). It is a widely accepted notion that a lack of theory of mind (ToM) as a basic social competence should be linked to higher aggression, but findings on the developmental links between ToM and different functions of aggression have been inconsistent. One reason for this may be the failure of taking the bi‐dimensionality of both ToM (cognitive vs. affective) and aggression (reactive vs. proactive) into account. In addition, the direction of effect remains unclear because longitudinal studies examining the mutual influences of both constructs are rare. Because research on ToM has focused on the preschool years, little is known about its development in middle childhood. Therefore, the present study examined the bi‐directional developmental links of cognitive and affective ToM with reactive and proactive aggression in a longitudinal study in N  = 232, 6‐ to 9‐year‐olds. Two points of measurement with a delay of about 1 year were conducted, and data were analyzed via cross‐lagged structural equation modeling (SEM), controlling for age, gender, and information processing. In general, early ToM predicted later functions of aggression, but not vice versa. Cognitive and affective ToM were inversely related to later reactive aggression, but only affective but not cognitive ToM was inversely related to later proactive aggression. These findings emphasize the importance of ToM for the occurrence of aggression and of taking the bi‐dimensionality of both constructs into account when investigating their developmental links across childhood.